Reeducación grafomotriz para la digrafía motora en los estudiantes de tercer año de educación básica de la unidad educativa Marieta de Veintimilla durante el periodo 2018-2019 - Pineda Orellana, Dayanara Alexandra (2019)
The research carried out regarding the difficulties of learning in students of school age, fundamentally at the elementary basic level, determines that motor dysgraphia is a learning disorder that makes it difficult or impossible to write correctly, significantly affects academic performance, becoming a problem, where the ignorance of strategies both at the teacher level and parents does not allow it to be adequately addressed, hence the need to develop an educational strategy based on the grafomotor reeducation for motor dysgraphia in third year students of basic education of the educational unit Marieta de Veintimilla. The research was descriptive, correlational and explanatory with a pre-experimental design, with a mixed quantitative-qualitative approach. Methods such as scientific, analytical, inductive, descriptive and statistical model were used. The TALE test was applied, which showed that of the 83 children investigated, 20 presented motor dysgraphia, which was intervened through grafomotor reeducation workshops, subsequently reapplied the test of literacy analysis, significantly reducing the reading by 90%. population with motor dysgraphia; what allows to conclude that the grafomotor reduction applied in an adequate and systematic way corrects the motor dysgraphia, for which reason the institution is recommended to train the teachers in the diagnosis and approach of the learning problems in the perspective of which the students improve their academic performance.